Orbits in static magnetically and dyonically charged Einstein-Euler-Heisenberg black hole spacetimes - Magos Cortes, Daniela (2023)
In the framework of the nonlinear Euler-Heisenberg electrodynamics coupled to general relativity, we consider static Einstein-Euler-Heisenberg magnetically and dyonically charged black hole spacetimes. These black holes are characterized, as usual, by mass M, magnetic charge Qm, electric charge Q and the Euler-Heisenberg nonlinear parameter. We find all possible equatorial trajectories for neutral and charged test particles. We analyze the light rings by using the Plebański pseudometric. The shape of the shadow of these black holes is presented, discussed, and compared with the one of the corresponding ReissnerNordström linear cases.